2016
DOI: 10.3892/ol.2016.5339
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 promotes hepatocellular carcinoma cell survival via CBR1 by suppressing TNF-α-induced ROS generation

Abstract: Abstract. It has been reported that intracellular accumulation of reactive oxygen species (ROS) has a significant role in tumor necrosis factor (TNF)-α-induced cell apoptosis and necrosis; however, the key molecules regulating ROS generation remain to be elucidated. The present study reports that knockdown of endogenous receptor for activated C kinase 1 (RACK1) increases the intracellular ROS level following TNF-α or H 2 O 2 stimulation in human hepatocellular carcinoma (HCC) cells, leading to promotion of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Recently, studies indicated that RACK1 plays a dramatic role in the occurrence, development, and metastasis of various cancers, including non-small-cell lung cancer [ 15 17 ], hepatocellular carcinoma [ 18 , 19 ], esophageal squamous cell carcinoma [ 20 , 21 ], breast cancer [ 22 , 23 ], and prostate cancer [ 24 , 25 ]. However, reports about the function of RACK1 in cancer are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies indicated that RACK1 plays a dramatic role in the occurrence, development, and metastasis of various cancers, including non-small-cell lung cancer [ 15 17 ], hepatocellular carcinoma [ 18 , 19 ], esophageal squamous cell carcinoma [ 20 , 21 ], breast cancer [ 22 , 23 ], and prostate cancer [ 24 , 25 ]. However, reports about the function of RACK1 in cancer are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Chen et al11 found that loss of RACK1 enhanced gastric cancer metastasis. Additionally, Deng et al proved that RACK1 suppressed gastric tumorigenesis 12. On the other hand, there were other kinds of research which demonstrated that RACK1 was found to promote lung cancer cell growth 13.…”
Section: Discussionmentioning
confidence: 99%
“…RACK1 is a small promiscuous scaffolding protein that interacts with many receptors and signaling molecules (Adams, Ron, & Kiely, 2011; Erbil et al, 2016; Zhao et al, 2015; Zhou et al, 2016). For example, in dopamine neurons, RACK1 binds to dopamine transporter (DAT) and regulates the DAT phosphorylation by protein kinase C (PKC) (Lee, Kim, Kim, & Lee, 2004).…”
Section: Nhe9 Cellular Functionsmentioning
confidence: 99%